The signaling pathways and targets of traditional Chinese medicine and natural medicine in triple-negative breast cancer - Yang, Zimei; Zhang, Qiuhua; Yu, Linghong; Zhu, Jiayan; Cao, Yi; Gao, Xiufei (Journal of ethnopharmacology, 2021)
Triple-negative breast cancer (TNBC) has a poorer prognosis than other subtypes due to its strong invasion and higher risk of distant metastasis. Traditional Chinese medicine (TCM) and natural medicine have the unique advantages of multitargets and small side-effects and may be used as long-term complementary and alternative therapies. Aim of the review: The present article summarizes the classical signaling pathways and potential targets by the action of TCM and natural medicine (including extracts, active constituents and formulas) on TNBC and provides evidence for its clinical efficacy. The literature information was acquired from the scientific databases PubMed, Web of Science and CNKI from January 2010 to June 2020, and it was designed to elucidate the internal mechanism and role of TCM and natural medicine in the treatment of TNBC. The search key words included “Triple negative breast cancer” or “triple negative breast carcinoma”, “TNBC” and “traditional Chinese medicine” or “Chinese herbal medicine”, “medicinal plant”, “natural plant”, and “herb”. We described the antitumor activity of TCM and natural medicine in TNBC based on different signaling pathways. Plant medicine and herbal formulas regulated the related gene and protein expression via pathways such as PI3K/AKT/mTOR, MAPK and Wnt/β-catenin, which inhibit the growth, proliferation, migration, invasion and metastasis of TNBC cells. The inhibitory effect of TCM and natural medicine on tumors was reflected in multiple levels and multiple pathways, providing reasonable evidence for new drug development. To make TCM and natural medicine widely and flexibly used in clinical practice, the efficacy, safety and mechanism of action need more in-depth experimental research. [Display omitted]